Leveraging Artificial Intelligence, Human Resource Information Systems, and People Analytics to Foster Organizational Sustainability in the Industry 5.0 Era - Sadikin; Nadira Nur Aisyah; Syahrial Shaddiq; Khuzaini; Zakky Zamrudi (Jurnal Riset Multidisiplin Edukasi, 2026)
The rapid advancement of digital technologies has transformed human resource management (HRM), making Artificial Intelligence (AI), Human Resource Information Systems (HRIS), and People Analytics essential tools for improving workforce management and organizational sustainability in the Industry 5.0 era. This study aims to examine how these digital technologies contribute to strategic HRM and sustainable organizational performance. This study uses a qualitative literature review approach by analyzing recent journal articles published between 2021 and 2026 from reputable databases, including Scopus, Web of Science, ScienceDirect, Emerald Insight, SpringerLink, and Taylor & Francis. The collected literature was analyzed using thematic analysis to identify key trends and best practices in digital HRM. The findings indicate that AI enhances recruitment, employee performance evaluation, and workforce planning. HRIS improves operational efficiency through integrated employee data management, while People Analytics supports data-driven decision-making by providing insights into employee performance, engagement, and retention. However, successful implementation depends on digital infrastructure, employee competencies, leadership support, and ethical data governance. The study concludes that integrating AI, HRIS, and People Analytics strengthens strategic human resource management and enhances organizational sustainability in the Industry 5.0 era. These findings provide practical insights for organizations seeking to accelerate digital transformation and achieve sustainable competitive advantage.